A generalization of surfaces family with common spatial geodesic - Kasap, Emin; Akyildiz, F. Talay; Orbay, Keziban (Applied mathematics and computation, 2008)
We analyzed the problem of constructing a surfaces family from a given spatial geodesic curve as in the work of Wang et al. [G.-J. Wang, K. Tang, C.-L. Tai, Parametric representation of a surface pencil with a common spatial geodesic, Comp. Aided Des. 36 (5) (2004) 447–459], who derived the sufficient condition on the marching-scale functions for which the curve C is an isogeodesic curve on a given surface. They assumed that these functions have a factor decomposition. In this work, we generalized their assumption to more general marching-scale functions and derived the sufficient conditions on them for which the curve C is an isogeodesic curve on a given surface. Finally using generalized marching-scale functions, we demonstrated some surfaces about subject.